Shared and Divergent Auditory and Tactile Processing in Children with Autism and Children with Sensory Processing Dysfunction Relative to Typically Developing Peers. (6th July 2015) - Demopoulos, Carly; Brandes-Aitken, Annie N.; Desai, Shivani S.; Hill, Susanna S.; Antovich, Ashley D.; Harris, Julia; Marco, Elysa J.
Abstract: The aim of this study was to compare sensory processing in typically developing children (TDC), children with Autism Spectrum Disorder (ASD), and those with sensory processing dysfunction (SPD) in the absence of an ASD. Performance-based measures of auditory and tactile processing were compared between male children ages 8–12 years assigned to an ASD ( N =20), SPD ( N =15), or TDC group ( N =19). Both the SPD and ASD groups were impaired relative to the TDC group on a performance-based measure of tactile processing (right-handed graphesthesia). In contrast, only the ASD group showed significant impairment on an auditory processing index assessing dichotic listening, temporal patterning, and auditory discrimination. Furthermore, this impaired auditory processing was associated with parent-rated communication skills for both the ASD group and the combined study sample. No significant group differences were detected on measures of left-handed graphesthesia, tactile sensitivity, or form discrimination; however, more participants in the SPD group demonstrated a higher tactile detection threshold (60%) compared to the TDC (26.7%) and ASD groups (35%). This study provides support for use of performance-based measures in the assessment of children with ASD and SPD and highlights the need to better understand how sensory processing affects the higher order cognitive abilities associated with ASD, such as verbal and non-verbal communication, regardless of diagnostic classification. ( JINS, 2015, 21, 444–454)